Tracking des transferts des bactéries porteuses de résistances entre animal, homme et environnement - Meyer, Sylvain; Laval, Lucie; Pimenta, Mélanie; González-Flores, Yolanda; Gaschet, Margaux; Couvé-Deacon, Elodie; Barraud, Olivier; Dagot, Christophe; Ploy, Marie-Cécile (Comptes Rendus Biologies, 2023)
The fight against antibiotic resistance must incorporate the “One Health” concept to be effective. This means having a holistic approach embracing the different ecosystems, human, animal, and environment. Transfers of resistance genes may exist between these three domains and different stresses related to the exposome may influence these transfers. Various targeted or pan-genomic molecular biology techniques can be used to better characterise the dissemination of bacterial clones and to identify exchanges of genes and mobile genetic elements between ecosystems.